O funcionamento de nomes próprios no processo de referenciação - Bassetto, Lívia Maria Turra [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The present work has as theoretical base the conception of referent presented by Textual Linguistics of socio-cognitive-interactionist base line. From this point of view, the referenciation is no longer seen as a relation of mirroring between language and reality, but as a process of referential construction that occurs in the discourse and, therefore, without a specular relation with the object of world. Hence, the referent has been considered object of discourse, since its construction occurs discursively whereof the verbal interaction, i.e., it is socio-culturally constructed starting from the social practices and remolded, in the interior of the discourse, in the function of the verbal interlocutors' comunicative purposes. Based on this theoretical support, this qualitative/interpretative research aimed to investigate the functioning of proper names, used in different contexts of verbal interaction, as strategies of referential construction, since there were no studies about it and only the designative function of the proper name was, without, therefore, (re)categorizing the referent. Differently from what the theory of Referenciation foresaw, this investigation aimed to demonstrate as, in particular situations of use, the proper name can be: (a) designative, in its more prototypic use; (b) attributive, being the characteristics constructed socio-cognitively in the verbal interaction; and (c) attributive, with more crystallized characteristics, being nearer the common name. Thus, these three modes of functioning of proper names constitute points of a continuum that starts from the designative proper name to the eponym - common name -, being the points (b) and (c) among them. To demonstrate these cases, texts of different genres (chronicles, newspaper reports, news, among others) were linguistically analyzed, emphasizing the use of proper names in different situations in the ...

O presente trabalho tem como base teórica a concepção de referente apresentada pela Linguística Textual de linha sócio-cognitivo-interacionista. Nessa perspectiva, a referenciação não é mais vista como uma relação de espelhamento entre linguagem e realidade, mas como um processo de construção referencial dada no interior do discurso e, portanto, sem relação especular com o objeto-de-mundo. Assim, o referente passa a ser considerado objeto-dediscurso, visto que sua construção se dá discursivamente a partir da interação verbal, ou seja, ele é construído sócio-culturalmente a partir das práticas sociais e remodelado, no interior do discurso, em função dos propósitos comunicativos dos parceiros da interlocução verbal. Com base nesse aparato teórico, esta pesquisa, de caráter qualitativo/interpretativo, buscou investigar o funcionamento de nomes próprios, empregados em diferentes contextos de interação verbal, como estratégia de construção referencial, já que não havia estudos a respeito e o nome próprio era considerado apenas com função designativa, sem, portanto, (re)categorizar o referente. Diferentemente do que previa a teoria da Referenciação, almejouse, com esta investigação, demonstrar como, em determinadas situações de uso, o nome próprio pode ser: (a) designativo, no seu uso mais prototípico; (b) atributivo, sendo as características construídas sociocognitivamente na interação verbal; e (c) atributivo, com características mais cristalizadas, de modo a estar mais próximo do nome comum. Assim, esses três modos de funcionamento do nome próprio constituem pontos de um continuum que parte do nome próprio designativo para o epônimo - nome comum -, estando os pontos (b) e (c) entre eles. Para demonstrar esses casos, foram analisados linguisticamente textos de variados gêneros (crônicas, reportagens, notícias, entre outros), ressaltando-se o emprego de nomes próprios em diferentes...
Keywords: Linguística; Análise linguística (Linguística); Referencia (Linguistica); Análise do discurso; Nomes